Differences in breast cancer survival and stage by age in off-target screening groups: a population-based retrospective studyAJOG Global Reports at a Glance - Juliana Oliveira Fernandes, PT, MSc; Cassio Cardoso-Filho, MD, PhD; Maria Beatriz Kraft, MD; Amanda Sacilotto Detoni, MD; Barbara Narciso Duarte, MD; Julia Yoriko Shinzato, MD, PhD; Diama Bhadra Vale, MD, PhD (Elsevier, 2023)
BACKGROUND: Age is an important prognostic factor in breast cancer. The target age to screen is under debate. OBJECTIVE: This study aimed to assess the influence of age on the diagnosis and survival among women with breast cancer. STUDY DESIGN: This was a retrospective cohort study of the Population-Based Cancer Registry of Campinas, Brazil, and included all women diagnosed from 2010 to 2014. The outcomes assessed were overall survival and stage. For statistical analyses, the Kaplan-Meier method, log-rank tests, and chi-square tests were used. RESULTS: The sample comprised 1741 women aged 40 to 79 years. Diagnoses at stages 0 to II were the more frequent. In the 40 to 49 years and 50 to 59 years age groups, the frequency of stage 0 (in situ) was 20.5% and 14.9% (P=.022), respectively, and the frequency of stage I was 20.2% and 25.8% (P=.042), respectively. The mean overall survival was 8.9 years (8.6-9.2) in the 40 to 49 years age group and 7.7 years (7.3-8.1) in the 70 to 79 years age group. The 5-year overall survival was higher in the 40 to 49 years age group than in the 50 to 59 years age group for stage 0 (in situ) (100.0% vs 95.0%; P=.036) and stage III (77.4% vs 66.2%; P=.046) diagnoses. The 5-year overall survival was higher in 60 to 69 years age group than in the 70 to 79 years age group for stages I (94.6% vs 86.5%; P=.002) and III (83.5% vs 64.9%; P=.010). In all age groups, significant differences in survival were not observed for stage 0 (in situ) vs stage I diagnoses, stage 0 vs stage II diagnoses, and stage I vs stage II diagnoses. CONCLUSION: Women aged 40 to 49 years had the highest proportion of in situ tumors, and stages III and IV accounted for about one-third of the cases in all age groups. There was no difference in the overall survival for stage 0 (in situ) vs stage I or II diagnoses in all age groups.